Anesthetic Management of a Patient with Fontan Physiology for Laparoscopic Cholecystectomy - Parajuli, Santosh Sharma (Nepalese Heart Journal, 2020)
With the modification in surgical techniques and advancement in medical sciences, the survival rate of patients with complex cardiac abnormalities has increased to more than 90% in about 10 years after Fontan palliation. These patients can present with some form of non-cardiac surgeries during their lifetime. Better understanding of Fontan physiology can help in proper perioperative anesthetic management of these patients. Our cases was of a 17-year-old female patient with Fontan physiology for her Ebstein’s Anomaly, planned for Laparoscopic Cholecystectomy under general anesthesia. Here we describe how we successfully managed the case perioperatively.